The TREatment of severe Atopic eczema Trial (TREAT). (3rd December 2018) - Irvine, A.D.; Jones, A.P.; Beattie, P.; Baron, S.; Browne, F.; Ashoor, F.; O'Neill, L.; Rosala‐Hallas, A.; Sach, T.; Spowart, C.; Taams, L.; Walker, C.; et al.
Summary: Atopic eczema is a skin disease affecting around 20% of UK children, 16% of whom have moderate to severe disease. Severe atopic eczema can cause sleep disturbance, poor school attendance and social withdrawal, as well as attention‐deficit hyperactivity disorder, anxiety and clinical depression. Skin can become infected and this can be a reason for hospital admission. Although most cases of atopic eczema can be treated with emollients, topical anti‐inflammatory treatments and/or ultraviolet (UV) therapy, around 2% of children require oral (taken by mouth) immuno‐suppressive treatment. The main treatment options of this type (called systemic agents) are Ciclosporin (CyA) and Methotrexate (MTX) and there is concern about their potential short‐ and long‐term side effects. This article explains an upcoming clinical trial called "The TREatment of severe Atopic eczema Trial" (TREAT). TREAT addresses key clinical questions for the management of children with severe atopic eczema using systemic medication, in particular whether there is a difference in speed of onset (how long the drug takes to start working), effectiveness, side‐effect profile and reduction in flares post‐treatment between CyA and MTX, and the cost‐effectiveness of the drugs. Furthermore, TREAT examines how both drugs go about reducing inflammation in the body and on the skin. The study will involve 102 children aged 2 to 16 years. Abstract : Linked Article: Irvine et al. Br J Dermatol 2018;179 :1297–1306